2014
DOI: 10.1086/678457
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolutionary Stage of the Interacting Binary AU Mon

Abstract: We present a study of the evolutionary stage of the interacting binary and Double Periodic Variable AU Mon. A multi-parametric χ 2 minimization is made between the observed parameters and those predicted by the grid of non-conservative and conservative evolutionary models by Van Rensbergen et al., finding the model that best represents the current stellar and system parameters. According to this model, the system started with initial masses 4 M and 3.6 M and orbital period 3.0 days, 196 million years ago, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…We found OGLE-LMC-T2CEP-211 to be similar to the AU Mon system (Mennickent 2014), with the exception that for OGLE-LMC-T2CEP-211 the initial period was longer and the mass transfer has finished, leaving a less massive donor on a much wider orbit around a very massive companion. The future of the AU Mon system may be similar (i.e.…”
Section: Summary and Discussionmentioning
confidence: 61%
“…We found OGLE-LMC-T2CEP-211 to be similar to the AU Mon system (Mennickent 2014), with the exception that for OGLE-LMC-T2CEP-211 the initial period was longer and the mass transfer has finished, leaving a less massive donor on a much wider orbit around a very massive companion. The future of the AU Mon system may be similar (i.e.…”
Section: Summary and Discussionmentioning
confidence: 61%
“…In this Section we compare the system parameters with those predicted by binary evolution models including epochs of nonconservative evolution following the method described by Mennickent (2014). The stellar and system parameters given by M15 were chosen as representative for the system, and are given in Table 2; in this paper we use subscript h and c for the hot and cool star, respectively.…”
Section: Evolutionary Stage Age and Mass Transfer Ratementioning
confidence: 99%
“…The interacting binary HD 170582 (BD-14 5085, ASAS ID 183048-1447.5, α 2000 = 18:30:47.5, δ 2000 = -14:47:27.8, V = 9.66 mag, B − V = 0.41 mag, spectral type A9V) 1 is a member of the class of Double Periodic Variables, Algol-related binaries showing a long photometric cycle lasting about 33 times the orbital period with a period ratio mostly between 25 and 45 (Mennickent et al 2003, Mennickent et al 2008, Poleski et al 2010, Mennickent et al 2012a, 2012b, Mennickent 2013, Garrido et al 2013, Barría et al 2013, 2014, Pawlak et al 2013. Recently, Mennickent et al (2016) showed that DPVs are those semi-detached Algols with Btype primaries of radius slightly larger than the critical radius 2 and also that they host stable accretion discs (Mennickent, Otero, & Kołaczkowski 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Mennickent (2014) proposes a (4 M + 3.6 M , P = 3 d) progenitor for AU Mon with a 1.533 M donor and a 6.067 M gainer at present. Since we model AU Mon towards a 1.2 M donor and a 7 M gainer our progenitors with initial mass ratio (4/3.6) need to have an initial orbital period a little below 1.4 d, determined from expression (12).…”
Section: Modeling the Starsmentioning
confidence: 93%